A qualidade do serviço no varejo supermercadista avaliada pelo RSQ (retail service quality) - Braga junior, Sergio Silva [UNESP]; Alonso junior, Nelson; Satolo, Eduardo Guilherme [UNESP] (My University, 2014)
The share of retail trade in the Brazilian economy, over time, has encouraged the development of national supermarket sector. As a result of this fact, the purchasing power of consumers and increase competitiveness in the sector have led retailers to seek new alternatives to offer their products to consumers. Because of this search, there was need to establish cooperation and coordination between retailers and suppliers in the development of efficient techniques for supply of goods as ECR (Efficient Consumer Response). Have the retailer in your store, seeks to add value to products through services and loyalty programs. In this sense, the objective of this study is to understand if consumers perceive the services provided by retail supermarket through the Retail Service Quality (RSQ). A survey was carried out among a sample of 212 individuals from São Paulo / SP / Brazil collecting responses directly in supermarkets after consumers make a purchase. As a result it was observed that the scale RSQ evaluate the quality of service in the retail market, and that the data obtained in the sample allow the diagnosis that the service provided by the retailer is perceived and evaluated by the consumer at the time this is provided. As a suggestion for further research is the application of RSQ scale in other retail or in a single network of retail market in order to assess the relationship between the constructs of the scale and quality of service offered by the retailer.
Service quality in retail supermarket reviewed by RSQ (retail service quality)
Keywords: Customer service; Quality of service; Retail